Direct bonding of crystalline components for application in high power laser systems - Rothhardt, Carolin; Risse, Stefan; Schreiber, Thomas; Eberhardt, Ramona; Rothhardt, Jan; Limpert, Jens; Tu¨nnermann, Andreas (Optics InfoBase Conference Papers, 2017)
Accumulated heat within optical crystals, like TGG or BBO, leads to unfavorable thermal lensing or even destruction. We propose distributing the heat by mechanically stable contacting the optical materials with transparent heat conductors (i.e. sapphire).
CRIS-Team Scopus Importer:2023-04-20